Application of lean management in medical laboratories to help treat patients with acute stroke - Nuoya Ma; Xiaofang Ding; Xudong Tang; Zhenzhu Xia; Qi Guo; Yan Yang; Kun Yan; Guoying Zou (Scientific Reports)
Abstract This study investigated the application effect of lean management in the treatment of acute stroke in medical laboratories and evaluated the impact on laboratory turnaround time (TAT) and operator satisfaction. In this study, 287 patients with acute stroke were selected from the Second People’s Hospital of Hunan Province and divided into a control group (129 cases, before lean management) and an experimental group (158 cases, after lean management). Lean management measures included establishing fast transfer channels, information management, optimisation of the centrifuge configuration, priority management, personnel training, use of the 6 S method, and visual management to optimise the process. The effects of lean management were evaluated by comparing the TAT of key inspection items using an operator satisfaction questionnaire. Lean management shortened the TAT for coagulation (21–18 min) and biochemical (33–29 min) tests (P = 0.000). Laboratory operators reported that lean management positively affects the overall performance of the laboratory. The application of lean management in medical laboratories can effectively improve the treatment efficiency of patients with acute stroke, shorten the TAT of key detection items, and provide high satisfaction among laboratory personnel.